Україна ранньомодерна в історіографії США і Канади (60-ті рр. ХХ – початок ХХІ ст.): теоретичні аспекти - Кудінов, Ю. (Український історичний збірник, 2011)
У статті розкрито періодизацію історичної науки США і Канади у дослідженні
ранньонової історії України. Узагальнено, що найбільший внесок у вивченні
ранньомодерної України здійснено україністичними центрами при Гарвардському та
Альбертському університетах. В статье указано периодизацию исторической науки США и Канады в изучении
истории Украины раннего нового времени. Обобщено, что наибольший вклад в изучение
истории Украины этого периода осуществлено украинистическими центрами при
Гарвардском и Альбертском университетах. In the article has enlightened the periodization of historical science in the USA and
Canada according to investigation of history of Early Modern Ukraine. It is summarized the
opinion that the greatest contribution to the examination of history of Ukraine in Early Modern
time were made by the centers of Ukrainian studies at Harvard University and the University of Alberta.